1047 The effect of exercise on heat tolerance and first lactation in pregnant Holstein heifers. (1st October 2016) - Johnson, J.; Steichen, P. L.; Rozell, T. G.
Abstract: A primary source of stress for dairy cattle is associated with the environment, particularly heat, and therefore a considerable amount of research has been done in an attempt to find ways of reducing heat stress. Exercise improves heat regulation in humans and horses; thus, the objectives of this study were to determine if an exercise regimen could improve thermo-tolerance and subsequent milk production during the hot part of the summer in Kansas. Pregnant Holstein heifers ( n = 24) were randomly assigned to 2 treatment groups: exercise (EX; n = 12), and exercise-control (EC; n = 12; walked with exercise heifers to exerciser but held in a holding pen). An exercise regimen was implemented through May and June, 4 d per wk in the afternoon for approximately 30–45 min using a motorized 8-panel walker. Data were collected on fitness test d 0, 28, and 56 of the experiment in which heifers were exercised for 23 min, 10 of which were spent at a greater intensity (5.63 KPH). Intra-vaginal temperature, skin temperature, respiration rates, and heart rate were recorded. Weekly measurements of skin temperature, respiration rates, and rectal temperatures were also recorded and post-parturition milk production and milk components were determined. All data were analyzed using PROC MIXED. Respiration rates and heart rates were not affected by exercise treatment on fitness test days or during weekly measurements ( P > 0.10). Time spent in body temperature zone 3 ( > 40.0°C) during the 23-min fitness test and 1 h following fitness test tended to be greater for EC than EX (87% vs. 76%; P < 0.10). Average body temperature of the hour following fitness tests was significantly less in EX than EC (40.48°C vs. 40.83°C; P < 0.05) on d 28. On fitness test Day 28, EX heifers tended to have reduced skin temperatures at the thurl post-exercise compared with EC ( P < 0.10). Exercised heifers had reduced skin temperatures of the cheek, withers, and thurl compared with EC during week 7 ( P < 0.05). Exercise resulted in greater milk protein % and solids-not-fat % ( P < 0.05) compared with EC, but there was no difference in monthly milk production in the first 150 d of lactation ( P > 0.10). These results indicate that exercise in pregnant dairy heifers may improve heat tolerance, and improve milk quality during first lactation.